PERILAKU MEMBELI PAKAIAN BEKAS (THRIFTING) PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PAKUAN, KOTA BOGOR - Kurnia, Muhammad Naufal Ihtifazhuddin; Khairulyadi, Khairulyadi (Gema Kampus IISIP YAPIS Biak, 2023)
Thrifting is an activity of shopping for used clothes with foreign brands that is currently popular, especially among young people. This consumption behavior is carried out by one of them by students, they buy foreign branded clothing (branded) but with used conditions (Thrifting) because it is considered cheaper but has good quality so that it creates a lifestyle. This study aims to provide an overview of how consumption behavior is carried out by Pakuan Bogor University students in buying used branded clothing (Thrifting). The method used in this research is qualitative with a phenomenological approach. Selection of sources using purposive sampling method. Data collection techniques were carried out by observation, interviews and documentation. The theory used in analyzing the data is the theory of consumption society by Jean Baudrillard. The results of the study show that Thrifting is a form of consumptive behavior of students of the Faculty of Economics and Business, Pakuan University, Bogor. The form of consumptive behavior is thrifting. Thrifting is a routine part of consumption for Unpak students because every time there is a new trend they will look for these clothes by thrifting either online or coming directly to the thrifting store. Thrifting is chosen because it is considered to be able to reduce prices and the quality offered is not much different from local products with new conditions. In addition, the comfort when used away.